Vesuvius, Etna, Stromboli, Vulcano: symbolic dimension of active volcanoes in southern Italy ; Vesubio, Etna, Stromboli, Vulcano: dimensión simbólica de volcanes activos en el sur de Italia - Ceruti, María Constanza (2025)
The altitude, shape, prominence and explosive manifestations of volcanoes in southern Italy have contributed to an elaborated traditional syncretism between preRoman, Roman and Christian beliefs; as well as religious rituals oriented to prevent or appease the destructive forces unleashed during eruptions. Mount Etna in Sicily and Fossa di Vulcano in the Aeolians appear in Classical mythology as the abode of Hephaestus, the Greek god of metalwork, later called Vulcano by the Romans. Constantly active for the last 2000 years, Stromboli is known as “the lighthouse of the Tyrrhenian”. Mount Epomeo and the hot springs on the island of Ischia are also interpreted in connection with the mythology of giants, which accounts for the secondary manifestations of volcanic activity in the Phlegraean Fields of the Gulf of Naples. This paper analyzes the symbolic dimension and religious role of active volcanoes in southern Italy, starting with the worldrenowned Vesuvius and its historic eruption, which covered in ashes and mud the Roman cities of Pompeii and Herculaneum. Additionally, venerated relics of Catholic saints, such as Saint Genaro or Saint Agatha, are also analyzed in connection to their protective role against the potentially destructive eruptions of Italian volcanoes. La altitud, la forma, la prominencia y las manifestaciones explosivas de los volcanes del sur de Italia han contribuido a un elaborado sincretismo tradicional entre las creencias prerromanas, romanas y cristianas, así como a rituales religiosos orientados a prevenir o apaciguar las fuerzas destructivas desatadas durante las erupciones. El monte Etna en Sicilia y la Fossa di Vulcano en las Eolias aparecen en la mitología clásica como la morada de Hefesto, el dios griego de la metalurgia, más tarde llamado Vulcano por los romanos. Activo de manera constante durante los últimos 2000 años, Stromboli es conocido como “el faro del Tirreno”. El monte Epomeo y las aguas termales de la isla de Ischia también se interpretan en relación con la mitología de los gigantes, que explica las manifestaciones secundarias de la actividad volcánica en los Campos Flégreos del golfo de Nápoles. Este artículo analiza la dimensión simbólica y el papel religioso de los volcanes activos en el sur de Italia, comenzando por el mundialmente famoso Vesubio y su histórica erupción, que cubrió de cenizas y lodo las ciudades romanas de Pompeya y Herculano. Además, también se analizan las reliquias veneradas de santos católicos, como san Genaro o santa Ágata, en relación con su papel protector contra las erupciones potencialmente destructivas de los volcanes italianos.